PENGUKURAN NILAI PERUSAHAAN DENGAN VARIABEL INTERN PERUSAHAAN PADA PERUSAHAAN SEKTOR INDUSTRI DI BURSA EFEK JAKARTA - Nina Agustina Rahmawati; Kundaru Hadiyato; Isnaeni Rokhayati (FEB UNWIKU PURWOKERTO, 2020)
This study is performed to examine the effect of Profitability, Dividend Policy, Firm Size, and Capital Structuretoward firm value in companies that is listed in Indonesian Stock Exchange over period 2011-2015. The population of this research is 37 company that listed in Indonesian Stock Exchange period 2011-2015. Sampling technique used here is purposive sampling on criterion (1) the company that represents their financial report per 2012-2014, (2) the company that have profit period 2011-2015 and (3) the company that continually share their dividend period 2011-2015. The data is obtained based on Indonesian Stock Exchange publication. It is gained sample amount of 12 companies from 37 companies those are listed in Indonesian Stock Exchange. The analysis technique used here is multiple regression with hypothesis test using t-statistic to examine partial regression coefficient and F-statistic to examine the mean of mutual effect with level of significance 5%. This research results show that simultaneouslyprofitability, dividend policy, firm size, and capital structure together influential on firm value .Partially profitability and dividend policy gives significantly positive effect on firm value, capital structure give significantly negative effect on firm value, and firm size give negative effect but not statistically significant. We suggest for management company in Indonesian Stock Exchange should be pay attention on profitability, dividend policy, and capital structure that gives significant effect in order to increase firm